KERJASAMA INDONESIA-KOREA SELATAN DALAM MENDUKUNG PROGRAM ONE VILLAGE ONE PRODUCT (OVOP) DI INDONESIA 2013-2015 - Era Riana; Den Yealta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The research aimed to study Indonesia-South Korea Cooporation in Condacting One Village One Product (OVOP) in 2013 to 2015. One Village One Product, the program is one of nation building.The research method used a qualitative and descriptive as a technique of research. Writer collected data from books, encyclopedia, journal, mass media, and websites to analyze “Indonesia-South Korea Cooporation in Condacting One Village One Product (OVOP) in 2013 to 2015”. The theories applied in this research are liberalism perspective and the decision making theory by Doughrety James and Pgaltzgrraff about Internasional Relations.Finally, Indonesia-South Korea cooperate in conducting One Village One Prodct (ovop) for economic relation and politic interest.Key words: One village One Product (ovop), national building.